Evaluation of Users’ Perception of President Buhari’s #Twitterban among Users in Anambra State - Chinelo Ebele Uchendu; Perpetua Ogechi Aondover; Omolara Oluwabusayo Akin-Odukoya; Louis Benard; Muhammad Ridwan (Britain International for Academic Research (BIAR) Publisher, 2025)
The advent of social networks such as Blogs, Facebook, Twitter, Instagram, WhatsApp, among others, has revolutionized communications. The power of social media messages rests on its ability to instantly and simultaneously reach a wide, diverse audience, and transforming social life. While the public has overtime become accustomed to the regulation of conventional media like the Radio, TV and Print establishments by government regulatory agencies, the idea of regulating social media, a space which many users consider to be the major avenue to air their views, is one that has generated mixed feelings. As such the Nigerian government has taken practical steps to regulate the activities of social media platforms including banning Twitter usage in Nigeria for a certain period. This study therefore, evaluated users’ perception of President Buhari’s #Twitterban among users in Anambra State. The study was anchored on Adaptive Structuration Theory and Public Sphere theory as its theoretical underpinnings. The study adopted survey method in carrying out the research with a sample size of 400 drawn from a population of 1,619,224 which was derived using the Taro Yamane’s formula. The Questionnaire was used as the instrument for data collection. The study found that the respondents have a negative perception about the #Twitter Ban by President Buhari as they stated that it was wrong to ban Twitter Usage in Nigeria and their freedom of speech were affected by the #Twitter Ban by President Buhari as they could not access Twitter to air their views, connect with friends to share opinion and to use other social media platforms.